CN Code as a Legal and Tax Standard - Drozdek, Adam (Acta Universitatis Lodziensis. Folia Iuridica, 2021)
The Excise Tax Act provides one of many forms of official tax law interpretations, i.e. the Binding Tariff Information. Pursuant to Article 7d, it is supposed to ensure the uniform application of the Excise Tax Act within taxation of excise goods or passenger cars, particularly by the interpretation that takes into consideration the classification in the system corresponding to the Combined Nomenclature (CN). Such interpretations are any General Rules for the Interpretation of the Combined Nomenclature and explanations of the customs tariff in accordance with the legal status as of the effective date of the Excise Tax Act, intended for the tax authorities and the Customs and Tax Service.